Negative inotropic and chronotropic effects on the guinea pig atrium of extracts obtained from Averrhoa carambola L. leaves - Vasconcelos,C.M.L. (2005)
It has been reported that star fruit can lead to a fatal outcome in uremic patients. The intoxication syndrome consists of hiccups, mental confusion, dizziness, and vomiting. On the other hand, folk medicine uses teas and infusions of carambola leaves to treat headache, vomiting, cough, insomnia, and diabetes. This motivated us to determine if Averrhoa carambola can act on the contractility and automaticity of the guinea pig heart. We measured the atrial isometric force in stimulated left atria and determined the chronotropic changes in spontaneously beating right atria. The carambola leaf extracts (1.5 mg/ml) abolished the contractile force in a concentration-dependent manner. Among the crude, methanolic, ethanolic, aqueous, and acetic extracts, the aqueous one was the most potent (EC50 = 520 ± 94 µg/ml; flavonoids and tannins are the main constituents; Na+ and K+ contents in 1.0 mg/ml of aqueous extract were 0.12 ± 0.016 and 1.19 ± 0.15 mM, respectively). The aqueous extract abolished the positive Bowditch staircase phenomenon and reduced the inotropic response to CaCl2 (0.17-8.22 mM), events that are dependent on the cellular Ca2+ inward current. The adrenergic, muscarinic or opioid membrane receptors do not seem to participate in the mechanism of action of the cardioactive substance(s). In spontaneously beating atria, the aqueous extract promoted a negative chronotropic effect that was antagonized by 0.1 µM isoproterenol bitartrate. With this agonist, the EC50 of the aqueous extract increased from 133 ± 58 to 650 ± 100 µg/ml. These data regarding the effect of A. carambola on guinea pig atrial contractility and automaticity indicate an L-type Ca2+ channel blockade.